2018
DOI: 10.1097/jnn.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adherence to Disease-Modifying Therapy in Patients With Multiple Sclerosis

Abstract: Patients' adherence to medication treatment was low and may be associated with social, physical, and cognitive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 4 publications
1
27
0
3
Order By: Relevance
“…MS specialists are aware of discontinuation in more than one in every 14 patients. Since physicians tend to over-estimate adherence in patients, and MS DMT adherence ranges from 46 to 97% in non-pandemic times [15][16][17], the number of people living with MS taking their DMTs on schedule is likely even lower than estimated here.…”
Section: Summary Of Qualitative Responsesmentioning
confidence: 78%
“…MS specialists are aware of discontinuation in more than one in every 14 patients. Since physicians tend to over-estimate adherence in patients, and MS DMT adherence ranges from 46 to 97% in non-pandemic times [15][16][17], the number of people living with MS taking their DMTs on schedule is likely even lower than estimated here.…”
Section: Summary Of Qualitative Responsesmentioning
confidence: 78%
“…Adherence to disease modifying agent (DMA) treatment is vital among patients with multiple sclerosis (MS) and is associated with positive clinical outcomes such as a reduction in relapses, progression of disability, and hospitalization. [1][2][3] Unfortunately, adherence to DMAs among patients with MS is often less than ideal ranging from 41%-88%. [4][5][6] In addition, early discontinuation of DMA is very common in MS; 9%-20% of patients discontinue DMA within six months from the date of initiation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Non-adherence to DMA leads to serious negative consequences such as increased relapses, progression of disability, and higher healthcare resource utilization, and significantly impacts the quality of life. 2,3,5,[7][8][9] Previous studies have found that adherence to DMAs is associated with factors related to the treatment route of administration, insurance coverage, patient and clinician. 8,9 The route of administration is one of the important factors associated with treatment adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MS are expected to take DMAs for at least 3 months to show a therapeutic response 46 . Therefore, adherence to DMAs in the initial period can play a significant role in treatment outcomes such as reducing relapses and in delaying the progression of MS 22,47–51 . Therefore, composite outcome evaluation was additionally done on a sub‐cohort who were adherent to DMAs during the first 3 months after DMA initiation (proportion of days covered [PDC] ≥0.8).…”
Section: Methodsmentioning
confidence: 99%